Chemical evaluation and thermal behavior of Brazil nut oil obtained by different extraction processes - Santos, O.V.; Corrêa, N.C.F.; Soares, F.A.S.M.; Gioielli, L.A.; Costa, C.E.F.; Lannes, S.C.S. (Food research international, 2012)
Brazil nut richness has been widely studied aiming at finding transformation models that increase its yield, keep its quality, reduce costs, and increase its productivity. The objective of this study is to evaluate the spectroscopic profile and the chemical and thermal behavior of Brazil nut oil obtained by different extraction processes. Lipid soxhlet extractions with petroleum ether and hexane, and using hydraulic pressing and supercritical carbon dioxide (CO2) were performed. The physicochemical analyses showed an acidity index with significant differences between the samples obtained by hydraulic pressing and supercritical CO2. The peroxide index presented significant difference for the oil obtained by hydraulic pressing compared to that obtained by the other extraction processes. The fatty acid profiles showed a relevant presence of the omega series (w-3, w-6, and w-9) with significant differences for the extraction processes evaluated. The results of the thermogravimetric and differential analyses did not indicate changes in mass loss and presented predominantly exothermic behavior. The spectroscopic profiles indicate that the extraction processes do not change the spectral profile of the oils. ► Techniques to preserve quality the oil and evaluate the thermal characteristics are subjects of intense research. ► We will study is to compare different processes of extraction of Brazil nut oil. ► The extraction processes evaluated in this study presented significant differences in the acidity and saponification indexes and variations between the fatty acid contents. ► The thermogravimetric and differential analyses show that the extractions studied did not change mass loss due to the peculiarities of the extraction process chosen.